1998
DOI: 10.1073/pnas.95.24.14168
|View full text |Cite
|
Sign up to set email alerts
|

Insulin depletion leads to adipose-specific cell death in obese but not lean mice

Abstract: Mutation of the obese gene produces obesity, hyperinsulinemia, and compensatory ''overexpression'' of the defective gene. As insulin activates obese gene expression, it seemed possible that hyperinsulinemia might be responsible for overexpression of the gene. To address this question we rapidly neutralized circulating insulin by injection of an insulin antibody. Unexpectedly, insulin depletion in obese (ob͞ob or db͞db) mice caused massive adipose RNA degradation confirmed by histological analysis to result fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Adipocytes in ob/ob mice are reported to be prone to apoptosis (47). Moreover, some markers of immature adipocytes such as adipocyte differentiation-related protein are increased (48).…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes in ob/ob mice are reported to be prone to apoptosis (47). Moreover, some markers of immature adipocytes such as adipocyte differentiation-related protein are increased (48).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial infiltration of inflammatory cells around necrotic-like adipocytes has been reported in experimental models of adipose cell death (2,9). In humans, the presence of CD68-positive macrophages in direct contact with mature adipocytes has been noted on adipose tissue slides (10).…”
mentioning
confidence: 98%
“…Resident macrophages are found in virtually all tissues (1). However, the presence of macrophages in white adipose tissue (WAT) has gone almost unnoticed, except for specific experimental conditions leading to adipose cell death in mice (2). It is now established that macrophages are scarce in the WAT of normal-weight individuals, but they increase markedly in animal models and in human obesity (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Apoptosis has been described both in WAT and brown adipose tissue (BAT) (Prins et al 1994). Several studies have demonstrated in vitro and in vivo adipocyte apoptosis under various conditions such as growth factor deprivation, dietary conjugated linoleic acid supplementation and streptozotocin administration , Loftus et al 1998, Miner et al 2001, Hargrave et al 2002. Even in patients with malignancy-associated weight loss, apoptosis is detected in abdominal, subcutaneous and omental fat (Prins et al 1994).…”
Section: Introductionmentioning
confidence: 99%